Managing and measuring capital : for banks and financial institutions - Ong, Michael K. (London : Risk Books, 2012)
This book concerns capital management, allocation, risk attribution and performance determination. As well as the measurement of capital. The book is essential for all who witnessed the devastating effects of the crisis, due fundamentally to undercapitalisation.
Includes bibliographical references and index.
oif 18/09/14
Loan
Keywords: Bank capital; Banks and banking; Securities industry